Fungal infections: immune defense, immunotherapies and vaccines - Loh, Jia Tong (2024)
Invasive fungal infection is an under recognized and emerging global health threat. Recently, the World Health Organization (WHO) released the first ever list of health-threatening fungi to guide research and public health interventions to strengthen global response to fungi infections and antifungal resistance. Currently, antifungal drugs only demonstrate partial success in improving prognosis of infected patients, and this is compounded by the rapid evolution of drug resistance among fungi species. The increased prevalence of fungal infections in individuals with underlying immunological deficiencies reflects the importance of an intact host immune system in controlling mycoses, and further highlights immunomodulation as a potential new avenue for the treatment of disseminated fungal diseases. In this review, we will summarize how host innate immune cells sense invading fungi through their pattern recognition receptors, and subsequently initiate a series of effector mechanisms and adaptive immune responses to mediate fungal clearance. In addition, we will discuss emerging preclinical and clinical data on antifungal immunotherapies and fungal vaccines which can potentially expand our antifungal armamentarium in future.